TINGKAT PENGETAHUAN SISWA SMA TENTANG KACAMATA KOREKSI SEBAGAI ALAT BANTU PENGLIHATAN - Novianti, Alisa; Subekti, Trisno; Hermawan, Heri (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
Correction glasses are one of the options in refractive error correction. Correction of refractive errors needs to be considered to obtain perfect sharp vision. The use of correction glasses in children must be done routinely, that is, worn at all times during school and other activities, especially reading. If the use is not routine or inaccurate, it will cause amblyopia, disrupt the learning process, decrease visual function and reduce quality of life. The purpose of this study was to determine the level of knowledge of Class XI students of SMA Negeri 1 Cikalongwetan about correction glasses as a visual aid. This type of research is descriptive quantitative with purposive sampling of 73 students. The results showed that based on the level of knowledge in class xi students totaling 73 students, it was found that the level of knowledge before being given education was mostly in the poor category, namely 42 respondents (58%), 24 respondents (33%) in the moderate category and 7 respondents (9%) in the good category. This causes many students to have refractive errors but they do not use glasses because many students do not know the important role of glasses as a visual aid.